Comparative analysis of choroidal thickness in third trimester pregnant women - Camila Zanella Benfica; Teresinha Zanella; Lucas Brandolt Farias; Maria Lúcia Rocha Oppermann; Luis Henrique Santos Canani; Daniel Lavinsky (International Journal of Retina and Vitreous, 2018)
Abstract Background The impact of pregnancy on the choroid is still under investigation. The aim of this study is to compare choroidal thickness measurements of healthy pregnant women in the third trimester and healthy non-pregnant women using spectral-domain optical coherence tomography (OCT). Methods This cross-sectional study included 122 eyes of 61 women, divided into two groups: 27 healthy pregnant women in the third trimester and 34 age-matched healthy non-pregnant women. Choroidal thickness was measured using Enhanced Depth Imaging OCT at ten different locations: at the fovea and every 500 µm from the fovea up to 2500 µm temporally and up to 2000 µm nasally. Results There were no significant differences in the ten measurements of choroidal thickness comparing both groups. Mean subfoveal choroidal thickness was 304.1 + 9.6 µm in the control group and 318.1 + 15.6 µm in the pregnant women group (p = 0.446). There was also no statistically significant association between gestational age and choroidal thickness measurements in the healthy pregnant women group. Conclusions Our study showed no statistically difference in choroidal thickness between healthy non-pregnant women and healthy pregnant women in the third trimester.